Understanding chemical short-range ordering/demixing coupled with lattice distortion in solid solution high entropy alloys. (1st September 2021) - He, Q.F.; Tang, P.H.; Chen, H.A.; Lan, S.; Wang, J.G.; Luan, J.H.; Du, M.; Liu, Y.; Liu, C.T.; Pao, C.W.; Yang, Y.
Abstract: Chemical short-range ordering (CSRO) or demixing in solid solution high entropy alloys (HEAs) is a fundamental issue yet to be fully understood. In this work, we first developed a generalized quasi-chemical solid solution model that enables quantitative computation of the local chemical ordering or demixing in solid solution HEAs. After that, we performed synchrotron diffraction experiments, extensive Reverse Monte Carlo (RMC) simulations, and first principles calculations on the CoCrFeNi model alloy to study the development of local chemical environments after long time thermal annealing. The outcome of the combined research demonstrates that the development of local chemical ordering or demixing in CoCrFeNi is not only affected by the heat of mixing between dislike atoms but also coupled with local lattice distortion. Graphical Abstract: Image, graphical abstract